Implementasi Tax Planning PPH Badan Atas Peredaran Bruto Sesuai PP No 55 Tahun 2022: (Studi Kasus PT. XYZ) - Fauziyyah, Ulfah; Suprihati; Rukmini (Nur Science Institute, 2025)
This study aims to analyze, evaluate, and compare the efficiency of corporate income tax burdens between the application of the Final Income Tax rate of 0.5% under Government Regulation No. 55 of 2022 and the general corporate tax rate stipulated in Article 17 with the facility of Article 31E of the Income Tax Law at PT. XYZ, a printing company with annual gross turnover below IDR 4.8 billion. The research employs a descriptive qualitative approach using the company’s 2022 financial statements and related tax documents as primary data. The results reveal that applying the final tax rate leads to tax payable of IDR 8,370,000, significantly lower than the general rate of IDR 20,976,395, creating a difference of IDR 12,606,395. In addition to financial efficiency, the final tax rate offers administrative simplicity as it does not require complex fiscal reconciliation. Nevertheless, the use of the final tax rate is limited to three years for limited liability companies, meaning the firm must prepare strategies for transitioning to the general tax regime in the future. These findings highlight that lawful and strategic tax planning is crucial to enhance financial efficiency while ensuring long-term compliance.